EXPLAINING THE ABSENCE OF CYBERWAR BETWEEN DEMOCRACIES: A DEMOCRATIC PEACE THEORY PERSPECTIVE - AKDAĞ, Yavuz (Cyberpolitik Journal, 2019)
Cyberwar defies the traditional concepts such as sovereignty and war, but little attention was paid by International Relations (IR) theory to studying cyber conflict. Most studies lacked analytical in-depth and systematicity. While some scholars have recently begun to systematically apply IR theory of realism and constructivism to cyberspace, IR scholars significantly ignored neo-liberal theories, especially Democratic Peace Theory (DPT). Thus, I intend to fill this theory-gap by offering a systematic and in-depth analysis using the DPT to explore how effectively it can explain the absence of cyberwar between democracies. I argue that despite the observed incidences of cyber conflict or cyberwar indicating the presence of peaceful cyber relations between democracies, this peaceful trend is unlikely to be a result of “democratic peace”, for the dynamics of cyberwar challenge the pacifying elements of normative and structural model of the theory. This hampers DPT`s cyber applicability. I used primary and secondary sources and drew on a case study—Stuxnet-, demonstrative empirical data, and theoretical and conceptual discussions in the relevant literature.